Bracing for a resurgence of Covid in a 3rd Wave: Uttarakhand Saga - Roy, Debabrata; Sinha, Richa; Deepshikha (Indian Journal of Community Health, 2021)
Evidently, the resurgence of COVID in a 2nd wave happened due largely to ‘Risk Compensation’ by the community, exacerbated by extreme risk behavior of the community. ‘Risk compensation’ or ‘Peltzman effect’, where there is an attitudinal shift underestimating the risk and subsequent complacency in observing due measures is almost an axiomatic phenomenon and this was being predicted in case of COVID too(1). However the scale, extent and intensity of the re-surgence (second wave) which was exponential & ‘asymptotic‘ was unwarranted, also unprecedented. That this re-surgence was a predictable phenomenon and needed pro-active & pragmatic strategizing/ decision making (which would affect community behavior vis a vis religious congregation and or other public events abetting gathering of crowd etc) was not unknown.